Microstructural investigation of the coatings prepared by simultaneous aluminizing and siliconizing process on γ-TiAl - Nouri S.; Azadeh M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this research, formation of aluminide/silicide diffusion coatings on γ-TiAl[Ti-48Al-2Nb–2Cr (at.%)] alloy using gasphase diffusion pack cementation process has been investigated. The application of powder mixtures with various chemical compositions in the pack cementation process performed at 1000oC for 6 hours in order to achieve simultaneous diffusion of Al and Si, showed that the composition of the powder mixture could have a significant effect on the structure and thickness of the aluminide/silicide coatings. The identification and analysis of aluminide/silicide microstructures formed as a result of simultaneous diffusion of Al and Si, which was comprehensively and qualitatively done for the first time in this study, showed that the sequential mechanism is dominant in the formation of the above-mentioned coatings. Furthermore, Kirkendall phenomenon and volumetric changes caused by the formation of Ti5Si3 and Ti5Si4, were considered as the two dominant mechanisms in the formation of porous segregated structure in these coatings. In this study, the effect of decreasing the activity of Si, through two approaches of reducing the amount of Si in the powder mixture and using Al- 20wt.%Si alloyed powder instead of pure Al and Si depositing elements, on the microstructural modification coatings was investigated. The results showed that reducing the Si activity at the surface of the coating and, consequently, reducing the flux of active silicon atoms (JSi), has a significant effect on the formation of coating with an ideal structure.